2009
DOI: 10.1152/japplphysiol.91443.2008
|View full text |Cite
|
Sign up to set email alerts
|

Decreased muscle ACE activity enhances functional response to endurance training in rats, without change in muscle oxidative capacity or contractile phenotype

Abstract: Habouzit E, Richard H, Sanchez H, Koulmann N, Serrurier B, Monnet R, Ventura-Clapier R, Bigard X. Decreased muscle ACE activity enhances functional response to endurance training in rats, without change in muscle oxidative capacity or contractile phenotype. J Appl Physiol 107: 346 -353, 2009. First published April 30, 2009 doi:10.1152/japplphysiol.91443.2008In the present study, we tested the hypothesis that chronic ANG I-converting enzyme (ACE) inhibition could improve the training-induced improvement in end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 34 publications
2
16
0
1
Order By: Relevance
“…The effect of these medications on the adaptation to training is unclear. Whereas some studies suggest that ACE activity may modify the adaptive response to training (69), more recent studies suggest that this is not related to modification of mitochondrial biology (19). Moreover, we should note that whether these medications affect mitochondrial structure/function is controversial (38,70), and there are no data regarding their effects on the mitochondrial adaptations to resistance training.…”
Section: Discussionmentioning
confidence: 93%
“…The effect of these medications on the adaptation to training is unclear. Whereas some studies suggest that ACE activity may modify the adaptive response to training (69), more recent studies suggest that this is not related to modification of mitochondrial biology (19). Moreover, we should note that whether these medications affect mitochondrial structure/function is controversial (38,70), and there are no data regarding their effects on the mitochondrial adaptations to resistance training.…”
Section: Discussionmentioning
confidence: 93%
“…However, in a small study of 36 older men with hypertension, endurance increased in those receiving ACEi (28), and our previous randomized controlled trial in functionally impaired people showed that 20 weeks of ACEi treatment significantly improved 6MWD by 31.6 m compared with placebo and resulted in a clinically significant improvement in quality of life (6). In rodents, improvements in performance with ACEi in combination with exercise but not with ACEi alone have been reported (29), but the evidence is not consistent (30,31). …”
Section: Discussionmentioning
confidence: 99%
“…13 Similarly, it was recently reported that the addition of ACEis potentiated exercise-mediated improvements in physical performance in older rats. 14,15 Both of these studies reported that the addition of ACEis potentiated the beneficial effects of aerobic training on exercise tolerance determined according to treadmill endurance. These preclinical findings add to an extensive literature from genetic studies of humans indicating an important interaction between the renin–angiotensin system and physical performance.…”
mentioning
confidence: 99%